In-Silico Structural and Functional Characterization of WsMYB44 Protein from Withania somnifera L. Dunal - Sharma, Lakee; Maurya, Bipin; Rai, Shashi Pandey (International Journal of Applied Sciences and Biotechnology, 2022)
The plant based MYB transcription factors have been extensively studied for structural and functional characterization. MYB protein is known to perform several molecular and biological processes including regulation of gene expression. In the current study, we have identified and characterized a R2R3 type MYB TF (WsMYB44) pertaining to root specific library from Withania somnifera. The phylogenetic studies of the identified protein sequence revealed its recent origin from Nicotiana sp., a member of Solanaceae family. Motif scans and domain analysis depicted strong conservation near signature R2 and R3 DNA binding domains which proved the specificity of the WsMYB44 protein. The modeled 3-D structure of protein showed significant binding affinity with the MYB binding DNA element C/TAACG/TG. The synergistic act of the predicted protein was proved by studying protein-protein interaction networks. Furthermore, Gene Ontology terms predicted nuclear localization of protein which was found to be involved in several defense related signaling cascades.